(Me4N)2O2CSO3Sn(O2CSO3)2.7Me4NSnCl5: SYNTHESIS AND INFRARED STUDY - Daouda Ndoye; Libasse Diop (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
On allowing Me4NO2CSO3H (in water) to react with SnCl4 (in ethanol) the studied complex is obtained. The suggested structure is discrete, the anion behaving as a polydentate and chelating ligand, the environment around tin being octahedral.